Acceptance And Use of E-Wallet Top-Up Feature Through Mobile Banking of Bank Syariah of Surakarta Muslim Society: UTAUT 2 Approach - Nurohman, Yulfan Arif; Qurniawati, Rina Sari; Anggraini, Vivin Puji (Islamic Banking : Jurnal Pemikiran dan Pengembangan Perbankan Syariah, 2025)
This study aims to identify factors that influence e-wallet top up via mobile banking at Islamic banks for Muslim communities in Surakarta using the UTAUT 2 approach. This study uses a quantitative approach to test and validate the formulated hypotheses. The population of this study were mobile banking users of Islamic banks in the Surakarta area. The sample determination was carried out using a purposive sampling technique, while the respondent criteria were Muslim communities in Surakarta City who had utilized mobile banking services at Islamic banks to top up e-wallets Data collection using questionnaires distributed to 150 Islamic bank customers. The data analysis technique used in this study was the Partial Least Squares (PLS) method which was carried out using SmartPLS software. The results showed that performance expectancy had an effect on behavioral intention, while other variables adopted from UTAUT 2 had no effect on behavioral intention. The contribution of the research findings indicates a shift in consumer preferences and behavior in using digital-based services.